2020
DOI: 10.1016/j.scitotenv.2020.138513
|View full text |Cite
|
Sign up to set email alerts
|

Impact of meteorological factors on the COVID-19 transmission: A multi-city study in China

Abstract: Absolute humidity Population migration m 3 , and one city (Haikou) had the highest AH (14.05 g/m 3 ). Those 17 cities with 50 and more cases accounted for 90.6% of all cases in our study. Each 1°C increase in AT and DTR was related to the decline of daily confirmed case counts, and the corresponding pooled RRs were 0.80 (95% CI: 0.75, 0.85) and 0.90 (95% CI: 0.86, 0.95), respectively. For AH, the association with COVID-19 case counts were statistically significant in lag 07 and lag 014. In addition, we found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

47
581
11
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 516 publications
(649 citation statements)
references
References 23 publications
47
581
11
10
Order By: Relevance
“…While some have documented the route of transmission through human-to-human contact, others have examined the role that some environmental factors may play in facilitating the rate of spread of the disease through the analysis of temporal and spatial relationships of these factors with COVID-19 transmission rate. Most of these studies have reported a negative relationship between transmission rate and several proxies of temperature and humidity, suggesting that the disease spread is enhanced in colder and drier climates [5][6][7][8][9] .Other environmental variables have received less attention and results have been inconclusive or differed among countries. For example, one study reported an inverse relationship between COVID-19 transmission and wind speed in Iran 10 , while global studies have found no signi cant association between both variables 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…While some have documented the route of transmission through human-to-human contact, others have examined the role that some environmental factors may play in facilitating the rate of spread of the disease through the analysis of temporal and spatial relationships of these factors with COVID-19 transmission rate. Most of these studies have reported a negative relationship between transmission rate and several proxies of temperature and humidity, suggesting that the disease spread is enhanced in colder and drier climates [5][6][7][8][9] .Other environmental variables have received less attention and results have been inconclusive or differed among countries. For example, one study reported an inverse relationship between COVID-19 transmission and wind speed in Iran 10 , while global studies have found no signi cant association between both variables 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…incidence (Liu et al 2020;Prata et al 2020;Qi et al 2020;Şahin 2020). SIR: social isolation rate; UV: ultraviolet radiation; T: temperature; RH: relative humidity; WS: wind speed; 3 : three days previous to case reports; 7 : seven days previous to case reports; 14 : fourteen days previous to case reports.…”
Section: Resultsmentioning
confidence: 99%
“…One recent review has addressed the role of climate change in the emergence and re-emergence of infectious diseases worldwide, indicating that temperature is an important environmental condition determining the success of infectious agents (El-Sayed and Kamel 2020). Furthermore, several studies have investigated the impact of weather on the COVID-19 transmission, with special attention to temperature and humidity (Liu et al 2020;Qi et al 2020;Şahin 2020;Wu et al 2020). Even though conducted in different countries and using distinct approaches, these investigations have indicated that temperature is inversely related to COVID-19 incidence.…”
Section: Introductionmentioning
confidence: 99%
“…Another related work is the work of Liu et al [8], who analyzed the impact of meteorological factors on COVID-19 in China's provinces. The results obtained from this study indicated that the transmission may be affected by factors such as low temperature, low humidity, and mild diurnal temperature range.…”
Section: Related Workmentioning
confidence: 99%